Fatigue management experiences from women undergoing chemotherapy: self-care strategies - Nayara Ferreira Cunha; Rosimár Alves Querino; Paula Carolina Bejo Wolkers; Anna Cláudia Yokoyama dos Anjos (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: In order to understand the experiences of women with breast cancer managing fatigue due to chemotherapy with the use of non-pharmacological strategies. Methods: Explanatory study, qualitative, with theoretical reference of medical anthropology and resources of the ethnographic method for data collection; in which four women took part. Thematic analysis was performed based on interviews and conducted observations. Results: Three strategies of self-care, resulted from the culture were used for physical fatigue management: rest, energy conservation and eat habits. Physical activities, contact with plants and religiosity were constituted as practices to deal with emotional fatigue. We understand that the meaning attributed to the use of non-pharmacological strategies was the possibility of feeling capable, confident and able to continue treatment. Conclusions and implications for practice: These woman's experiences revealed the following necessities, the use of specific strategies to deal with fatigue, as well as the appreciation and understanding of their singularities and cultural practices present in their contexts. In the nursing care, it is possible to associate these practices with scientific knowledge and thus complement the care in favor of an integral care.